2009
DOI: 10.1016/j.cell.2009.06.033
|View full text |Cite
|
Sign up to set email alerts
|

A Synaptic Vesicle-Associated Ca2+ Channel Promotes Endocytosis and Couples Exocytosis to Endocytosis

Abstract: Summary Synaptic vesicle (SV) exo- and endocytosis are tightly coupled to sustain neurotransmission in presynaptic terminals, and both are regulated by Ca2+. Ca2+ influx triggered by voltage-gated Ca2+ channels is necessary for SV fusion. However, extracellular Ca2+ has also been shown to be required for endocytosis. The intracellular Ca2+ levels (< 1μM) that trigger endocytosis are typically much lower than those (> 10μM) needed to induce exocytosis, and endocytosis is inhibited when the Ca2+ level exceeds 1μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(208 citation statements)
references
References 66 publications
11
193
4
Order By: Relevance
“…Indeed, pharmacological manipulations at the Drosophila melanogaster neuromuscular junction 93,94 imply the existence of a specific Ca 2+ channel for synaptic vesicle endocytosis. whether this channel is identical to the recently identified Drosophila melanogaster synaptic vesicle protein known as flower is not yet proven 76 . Differential sensitivity to Ca 2+ buffers suggests that local microdomain Ca 2+ created by multiple channels also underlies slow endocytosis at the calyx of Held 34,95 .…”
Section: Calcium Regulationmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, pharmacological manipulations at the Drosophila melanogaster neuromuscular junction 93,94 imply the existence of a specific Ca 2+ channel for synaptic vesicle endocytosis. whether this channel is identical to the recently identified Drosophila melanogaster synaptic vesicle protein known as flower is not yet proven 76 . Differential sensitivity to Ca 2+ buffers suggests that local microdomain Ca 2+ created by multiple channels also underlies slow endocytosis at the calyx of Held 34,95 .…”
Section: Calcium Regulationmentioning
confidence: 98%
“…At concentrations well below the threshold for exocytosis, Ca 2+ may facilitate endocytosis in model systems such as the lamprey reticulospinal synapse 74 . Recently, the synaptic vesicleassociated transmembrane protein known as flower (a proposed Ca 2+ channel) was shown to regulate synaptic vesicle endocytosis, and thus, potentially control exocytic-endocytic coupling 76 . However, the role of Ca 2+ may actually be supportive rather than mandatory, because endocytosis was found to be intact in hippocampal nerve terminals at resting Ca 2+ levels after sucrose-induced release 77 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…However, hydropathy plot analysis indicated that these proteins may share three to four membrane-spanning domains, and may localize to the plasma membrane of papilla cells, where the interaction between pollen and stigma cells occurs. The structural features of SE proteins are similar to the predicted structure of PrpS proteins, the female determinant of SI of Papaver (Wheeler et al 2009 ), and the fl ower protein of Drosophila (Yao et al 2009 ;Brose and Neher 2009 ), which may act as a Ca 2+ channel in synaptic endocytosis (Fig. 25.11 ).…”
Section: Genes Located At or Near The S -Locus Of I Trifi Damentioning
confidence: 63%
“…An intriguing possibility has emerged. A novel Drosophila protein, Flower, which functions in presynaptic vesicle endocytosis, has recently been characterized (Yao et al 2009 ). Both Flower and PrpS are novel proteins with no obvious homologues and have very little primary sequence homology.…”
Section: The Pollen S -Locus Determinantsmentioning
confidence: 99%
“…However, they have similar topological predictions, so are "topological homologues." The Flower protein functions as a Ca 2+ -permeable channel (Yao et al 2009 ). Voltagegated calcium channels have acidic amino acids (either glutamic acid or aspartic acid) in the transmembrane domains that form a pore.…”
Section: The Pollen S -Locus Determinantsmentioning
confidence: 99%